Transcriptome Analyses Reveal Systematic Molecular Pathology After Optic Nerve Crush - Pan, Yuan-Bo; Sun, Yiyu; Li, Hong-Jiang; Zhou, Lai-Yang; Zhang, Jianmin; Feng, Dong-Fu (Frontiers in Cellular Neuroscience, 2022)
The function of glial cells in axonal regeneration after injury has been the subject of controversy in recent years. Thus, deeper insight into glial cells is urgently needed. Many studies on glial cells have elucidated the mechanisms of a certain gene or cell type in axon regeneration. However, studies that manipulate a single variable may overlook other changes. Here, we performed a series of comprehensive transcriptome analyses of the optic nerve head over a period of 90 days after optic nerve crush (ONC), showing systematic molecular changes in the optic nerve head (ONH). Furthermore, using weighted gene coexpression network analysis (WGCNA), we established gene module programs corresponding to various pathological events at different times post-ONC and found hub genes that may be potential therapeutic targets. In addition, we analyzed the changes in different glial cells based on their subtype markers. We revealed that the transition trend of different glial cells depended on the time course, which provides clues for modulating glial function in further research.